An Assessment of Soil Fertility Status in Chambal Commanded Area - Sharma, C. P.; Seth, S. P.; Singh, Harvinder (Indian Forester, 1972)
The soil fertility map showing the available nutrient status of the Chambal Commanded area has been prepared and fertilizer recommendations for various crops have been given. This map is based on the analysis of 3793 soil samples collected by random sampling of villages under the command of Chambal Project. Nutrient index values are used to indicate fertility status of soils of a Tehsil for the purpose of mapping.